PERAN KADER POSYANDU DALAM PENCEGAHAN STUNTING DI DESA BOTUWOMBATO KECAMATAN KWANDANG KABUPATEN GORONTALO UTARA - Anuna, Sitria Komaria; Nggilu, Rukiyah; Gintulangi, Sabriana Oktaviana (STISIPOL Mujahidin Buol, 2023)
This research aims to determine the role of Posyandu cadres in preventing stunting in Botuwombato Village, Kwandang District, North Gorontalo Regency. This research consists of three focuses, namely Socialization, Facilitator, and Educator. The research method used is descriptive qualitative. The research results concluded that the socialization role of Posyandu cadres was not optimal. This can be seen from socialization activities that are situational in nature and not carried out intensively. The role of the Posyandu cadre facilitator is optimal. This can be seen from the alert attitude of the Posyandu cadres in providing assistance to people in need, especially to the target group, namely breastfeeding mothers, pregnant mothers and mothers with babies and toddlers. The educational role of Posyandu cadres is not optimal, this is because the average level of education of Posyandu cadres is still low.